Three-axis piezoresistive accelerometer with adjustable axial resolutions - Hang, Bui Thu; Tan, Tran Duc; Trinh, Chu Duc (Vietnam Journal of Mechanics, 2012)
A three-axis piezoresistive accelerometer which has adjustable resolutions to three axes was developed using MicroElectroMechanical Systems (MEMS) technology. This sensor made of a heavy proof mass and four long beams is to obtain high resolutions by reducing resonance frequencies. Adjustable resolution with small cross axis sensitivity could be obtained by a three-dimensional sensor structure.